Synthesis of β-FeOOH/TiO2/SiO2 by melting phase separation-hydrothermal method to improve photocatalytic performance. Issue 22 (15th November 2021) - Dong, Xiaozhu; Xu, Jinbo; Kong, Cunhui; Zeng, Xiongfeng; Wang, Jiansheng; Zhao, Yingna; Zhang, Wenli
Abstract: This paper combines traditional ceramics with advanced ceramics, based on the principle of matching the phase separation temperature of the Na2 O–B2 O3 –SiO2 glass system with the crystallization temperature of TiO2, and uses the melting-phase separation method to directly separate the TiO2 photocatalytic material from the porous glass. The catalyst is tightly combined with the SiO2 carrier, and then the β-FeOOH/TiO2 /SiO2 composite material is prepared by the hydrothermal method. X-ray diffraction (XRD), scanning electron microscope (SEM), transmission electron microscope (TEM), infrared spectroscopy (FT-IR) and specific surface area (BET) were used to analyze the crystal structure, morphology and phase composition of the compound. Ultraviolet–visible diffuse reflectance spectroscopy (UV–vis DRS) and photoluminescence spectroscopy (PL) are used to characterize the light absorption characteristics of samples. Using tetracycline hydrochloride as a simulated degradation product, the photocatalytic activity of the composite photocatalyst under visible light was studied. The experimental results show that the double-crystal phase glass-ceramics are prepared by the melting phase separation method, the crystal phase is TiO2, and the amorphous phase is SiO2 . A heterojunction was successfully constructed between β-FeOOH and TiO2, which effectively improved the migration efficiency of photogenerated carriers and extended the light response range to 640 nm. The photocatalytic efficiency of 0.2β-FeOOH/TiO2 /SiO2 composite photocatalyst to tetracycline hydrochloride (TC) is 77 %. After 3 cycles of photocatalytic degradation test, the composite material still maintains good photocatalytic performance, and the crystal structure has not changed. Superoxide free radicals are the main active substance that degrades TC. This provides a reference for the industrial production of glass-phase TiO2 -based composite photocatalyst. Highlights: The glass crystallites with two phases were prepared by the melting phase separation method. The mechanism of β-FeOOH/TiO2 /SiO2  was analyzed.